Phase transformations in the system Cu-Zn-Al under conditions far from equilibrium; AIP Conference Proceedings; Vol. 1698 : Advanced materials in technology and construction: AMTC-2015 - Klopotov A. A. Anatoly Anatoljevich; Ivanov Yu. F. Yuriy Fedorovich; Vlasov V. A Viktor Alekseevich; Dedov N. V. Nikolay Vladimirovich; Loskutov L. G. Leonid Gennadjevich (2016, 2016)
Title screen